Pro- and Antiapoptotic Markers in Upper Tract Urothelial Carcinoma Associated with Balkan Endemic Nephropathy - Ljubinka Jankovic-Velickovic; Slavica Stojnev; Ana Ristic-Petrovic; Zana Dolicanin; Takanori Hattori; Kenichi Mukaisho; Mariola Stojanovic; Vladisav Stefanovic (The Scientific World Journal)
The role of aristolochic acid in the etiology of Balkan endemic nephropathy (BEN) and associated upper-tract urothelial carcinoma (UTUC) has been recently confirmed. The aim of this study was to determine apoptosis-related marker(s) specific for BEN-associated UTUC. Present investigation included 105 patients with UTUC, 44 from BEN region and 61 control tumors. Altered expression of Survivin was more often present in BEN UTUC with high grade and solid growth (P<0.005; P<0.05) than in control tumors. Significantly lower expression of proapoptotic marker Bax was found in BEN tumors with high grade, high stage, necrosis, and without metaplastic change (P<0.05; 0.05; 0.05; 0.05) compared to control tumors with the same features. Group (BEN-related/control), stage, growth pattern, and caspase 3 activity were significantly associated with the expression of Bax (P=0.002, 0.034, 0.047, 0.028, resp.,). This investigation identifies Bax as specific marker of BEN-associated UTUC. Decrease of pro-apoptotic protein Bax together with alteration of Survivin may be indicative for specific disturbances of intrinsic apoptotic pathway in UTUC arising in endemic areas.